PENGARUH SIKAP KERJA, BEBAN KERJA YANG DIBAWA, INDEKS MASSA TUBUH DAN FLEKSIBILITAS LUMBAL TERHADAP KELUHAN NYERI PUNGGUNG BAWAH PADA BURUH ANGKAT DI PASAR INDUK JAKARTA TIMUR - Bestari Pangestuti (2021)
Health problems for workers often arise because of their work. One of the most common health problems affecting the entire population is low back pain. Lower Back Pain (LBP) is a common musculoskeletal symptom that may be acute or chronic. There are several risk factors for developing LBP, including high body mass index (BMI) (overweight or obese), heavy workload, work attitude and several other factors. A decrease in individual body function is often found in people with NPB complaints which are characterized by a decrease in lumbar flexibility. So an analysis of the risk factors for the occurrence of LBP is needed. This research is a cross sectional study on 72 respondents using a questionnaire and physical examination. Data were analyzed using the chi square test and logistic regression test. The results showed that work attitude, work load carried and BMI had an influence on LBP complaints with each p value of work attitude (p value = 0.025), work load carried (p value = 0.017), BMI (p value = 0.023). Meanwhile, the results of the research on lumbar flexibility showed no effect on complaints of NPB with p value (p value = 0.338). of the three variables that can influence NPB complaints. The overall percentage shows the effect of LBP complaints by 69.4%. In conclusion, work attitude, workload carried, BM can affect NPB complaints. Respondents must pay attention to their attitude at work, pay attention to the weight of the load in accordance with national statutory standards and monitor their body weight to fit the normal BMI category.